EXAMINING HOW ENGLISH TEACHERS' REQUESTS ARE USED IN INTERACTIONS WITH STUDENTS IN INDONESIAN CLASSROOMS - Hasanah, Nurul; Mahmud, Murni (Universitas Negeri Makassar, 2023)
This study aims to investigate the request expressions that English teachers use during EFL classroom interactions. It is essential to use requests in the classroom to foster productive student interaction. Teachers can encourage politeness and discourage unpleasant behavior in the classroom by using requests. This study is qualitative in nature. It was held at a single senior high school in Pangkep, Indonesia's South Sulawesi. Four English teachers are the research subjects. The teaching methods of the four teachers were videotaped, written down, and examined in order to gather data. Four lengthy snippets of the teaching process were recorded, then examined to investigate the request expressions that instructors employ out of courtesy. The information gathered was examined using the politeness procedures proposed by Brown and Levinson (1987). The study's findings demonstrate that educators used bald, negative, and positive on-record techniques in accordance with Brown and Levinson's theory (1987). Teachers utilize terms like